Blood pressure changes during twin pregnancies: the Japan Environment and Children's Study. Issue 1 (January 2019) - Iwama, Noriyuki; Metoki, Hirohito; Nishigori, Hidekazu; Mizuno, Satoshi; Takahashi, Fumiaki; Tanaka, Kosuke; Watanabe, Zen; Saito, Masatoshi; Sakurai, Kasumi; Ishikuro, Mami; Obara, Taku; Tatsuta, Nozomi; et al.
Abstract : Objectives: Although a twin pregnancy is a risk factor for hypertensive disorders of pregnancy, studies investigating longitudinal blood pressure changes during twin pregnancies are uncommon. The aims of this study were to evaluate the longitudinal blood pressure changes during twin pregnancies and to compare blood pressure levels between twin and singleton pregnancies. Methods: Five hundred dichorionic diamniotic twin, 240 monochorionic diamniotic twin, and 80 775 singleton pregnancies were included in this Japanese prospective birth cohort study. A marginal model was applied to evaluate the SBP, DBP, and mean arterial pressure levels during early gestation, mid-gestation, and late gestation. Results: The blood pressure levels fell from early-to-mid-gestation and rose after mid-gestation in the dichorionic and monochorionic diamniotic twin pregnancies. The SBP and mean arterial pressure levels during early gestation and the DBP and mean arterial pressure levels during late gestation were higher in the dichorionic diamniotic twin pregnancies than those in the singleton pregnancies. The blood pressure levels in the monochorionic diamniotic twin pregnancies were higher than those in the singleton pregnancies at each gestational stage, except for the SBP during late gestation. Conclusion: Although the longitudinal blood pressure changes during twin pregnancies were similar to those during singleton pregnancies, the blood pressure levels during twin pregnancies were higher. Further studies that examine the associations between the longitudinal blood pressure changes during pregnancy and the perinatal outcomes in twin pregnancies are necessary. Abstract : Supplemental Digital Content is available in the text